Oxysterol signaling in the central nervous system: cellular mechanisms and implications for neurodegeneration - Ricci, Raphael P.; Foo, Cheng Xiang; Ronacher, Katharina; Cullen, Carlie L. (Frontiers in Molecular Neuroscience, 2026)
Oxysterols, oxidized derivatives of cholesterol, are key modulators of central nervous system (CNS) function. Acting as both signaling molecules and cytotoxic mediators, oxysterols can influence glial activity, neuroinflammation and myelination. Glial cells (astrocytes, oligodendrocytes, and microglia) maintain neuronal homeostasis, support synaptic plasticity and mediate CNS repair. Dysregulated glial function contributes to chronic neuroinflammation, a hallmark of neurodegenerative and neuropsychiatric disorders such as Alzheimer’s disease, Parkinson’s disease and multiple sclerosis. In this review article, we discuss the roles of oxysterols in the CNS with a particular focus on their impact on glial cells, neuroinflammation, myelination and neural circuit function. Therapeutically targeting oxysterol metabolism may mitigate oxidative stress, limit apoptosis, enhance glial health and influence myelin repair. Elucidating oxysterol signaling in glia and neurons provides critical insight into neural circuit regulation and identifies promising strategies for treating demyelinating, neurodegenerative and neuropsychiatric disorders.